2022
DOI: 10.1101/2022.10.17.22281183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Monkeypox disease knowledge and perception among the healthcare workers versus the general population during the first month of the WHO emerging infectious disease alert

Abstract: Background: Monkeypox disease (MPD) recently re-emerged in May 2022 and caused international outbreaks in multiple non-endemic countries. This study aimed to assess the Saudi Arabian public and healthcare workers (HCWs) knowledge about MPD and their information-seeking attitudes before any cases were yet reported in Saudi Arabia. Methods: This online survey of HCWs and the public in the Kingdom of Saudi Arabia (KSA) was conducted from May 27 to June 5, 2022. The survey tool was adopted from our published resea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…From the foregoing, it is pertinent that improving the knowledge and perception of healthcare workers through have more interest in acquiring information, read scientific journals, and ensuring participation in training and retraining not only improve their knowledge but also raise the perception index towards ensuring safety measures are further strengthened. 31,32 On the safety practices and preventive measures by healthcare workers, our current study observed that 98.3% agreed that the use of personal protective equipment (PPE) is necessary while attending to patient with rash, also 98.3% agreed that exposed people with symptoms of fever, headache and rash should have blood samples taken for PCR testing and 96.3% admitted patients should be hospitalized in the isolation room, preferably with restriction of contact with other patients.…”
Section: Discussionmentioning
confidence: 77%
“…From the foregoing, it is pertinent that improving the knowledge and perception of healthcare workers through have more interest in acquiring information, read scientific journals, and ensuring participation in training and retraining not only improve their knowledge but also raise the perception index towards ensuring safety measures are further strengthened. 31,32 On the safety practices and preventive measures by healthcare workers, our current study observed that 98.3% agreed that the use of personal protective equipment (PPE) is necessary while attending to patient with rash, also 98.3% agreed that exposed people with symptoms of fever, headache and rash should have blood samples taken for PCR testing and 96.3% admitted patients should be hospitalized in the isolation room, preferably with restriction of contact with other patients.…”
Section: Discussionmentioning
confidence: 77%